First-principles insights into the optoelectronic, thermoelectric, and elastic properties of Cs2NaSbBr6 double perovskites for sustainable energy applications - MD Ratul Hasan; Imtiaz Ahamed Apon; Md. Alamgir Hossain (AIP Advances)
In this study, first-principles calculations were performed by different functionals to investigate the structural, electronic, and optical properties of Cs2NaSbBr6 double perovskite using density functional theory. The computed lattice constants a = 8.220 Å, Generalized Gradient Approximation-Perdew–Burke–Ernzerhof (GGA-PBE), unit cell volume, V = 392.789 Å3, and formation enthalpy, ΔEf = −1431.59 eV/atom, confirm the structural stability and thermodynamic feasibility of the material. The tolerance factor τ = 0.810 further supports its structural robustness. The electronic structure analysis reveals a bandgap of 2.820 eV (GGA-PBE), indicating its potential for optoelectronic applications. The band structure and density of states (DOS) calculations provide insights into its electronic properties. Partial DOS was also used to discuss the bonding nature and strength among the different states. The optical properties of these phases have also been computed and analyzed to reveal possible relevance in diverse fields. Optical properties, including strong absorption in the visible spectrum, suggest its suitability for photovoltaic and energy-harvesting applications. The findings of this study highlight Cs2NaSbBr6 as a promising candidate for future experimental and technological advancements in renewable energy applications.